Tailoring implementation strategies for scale-up: Preparing to take the Med-South Lifestyle program to scale statewide - Leeman, Jennifer; Draeger, Lindy B.; Lyons, Kiira; Pham, Lisa; Samuel-Hodge, Carmen (Frontiers in Health Services, 2022)
Abstract Background. Tailoring implementation strategies for scale-up involves engaging stakeholders, identifying implementation determinants, and designing implementation strategies to target those determinants. The purpose of this paper is to describe the multiphase process used to engage stakeholders in tailoring strategies to scale-up the Med-South Lifestyle Program, a research-supported lifestyle change intervention that translates the Mediterranean dietary pattern for the southeastern U.S. Methods. Guided by Barker et al.’s (2016) framework, we tailored scale-up strategies over four-phases. In Phase 1, we engaged stakeholders from delivery systems that implement lifestyle interventions and from support systems that provide training and other support for statewide scale-up. In Phase 2, we partnered with delivery systems (community health centers and health departments) to design and pilot test implementation strategies (2014-2019). In Phase 3, we partnered with both delivery and support systems to tailor Phase 2 strategies for scale-up (2019-2021) and are now testing those tailored strategies in a type 3 hybrid study (2021-2023). This paper reports on the Phase 3 methods used to tailor implementation strategies for scale-up. To identify determinants of scale-up, we surveyed delivery systems (n=114 community health centers and health departments) and elicited input from delivery and support system stakeholders. We tailored strategies to address identified determinants by adapting the form of Phase 2 strategies while retaining their functions. We pilot tested strategies in three sites and collected data on intermediate, implementation, and effectiveness outcomes. Findings. Determinants of scale-up included limited staffing and safety concerns during COVID-19, among others. Tailoring yielded two levels of implementation strategies. At the level of the delivery system, strategies included implementation teams, an implementation blueprint, and cyclical small tests of change. At the level of the support system, strategies included training, educational materials, quality monitoring, and technical assistance. Findings from the pilot study provide evidence for the implementation strategies’ reach, acceptability, and feasibility, with mixed findings on fidelity. Strategies were only moderately successful at building delivery system capacity to implement Med-South. Conclusions: This paper describes the multiphase approach used to plan for Med-South scale-up, including the methods used to tailor two-levels of implementation strategies by identifying and targeting multilevel determinants.